Paramedic use of the Physician Order for Life-Sustaining Treatment (POLST) for medical intervention and transportation decisions - Amelia M. Breyre; Karl A. Sporer; Glen Davenport; Eric Isaacs; Nicolaus W. Glomb (BMC Emergency Medicine, 2022)
Abstract Background Physician Order for Life-Sustaining Treatment forms (POLST) exist in some format in all 50 states. The objective of this study is to determine paramedic interpretation and application of the California POLST for medical intervention and transportation decisions. Methods This study used a prospective, convenience sample of California Bay Area paramedics who reviewed six fictional scenarios of patients and accompanying mock POLST forms. Based on the clinical case and POLST, paramedics identified medical interventions that were appropriate (i.e. non-invasive positive pressure airway) as well as transportation decisions (i.e. non-transport to the hospital against medical advice). EMS provider confidence in their POLST interpretation was also assessed. Results There were 118 paramedic participants with a mean of 13.3 years of EMS experience that completed the survey. Paramedics routinely identified the selected medical intervention on a patients POLST correctly as either comfort focused, selective or full treatment (113-118;96%-100%). For many clinical scenarios, particularly when a patient’s POLST indicated comfort focused treatment, paramedics chose to use online medical oversight through base physician contact (68-73;58%-62%). In one case, a POLST indicated “transport to hospital only if comfort needs cannot be met in current location”, 13 (14%) paramedics elected to transport the patient anyway and 51 (43%) chose “Non-transport, Against Medical Advice”. The majority of paramedics agreed or strongly agreed that they knew how to use a POLST to decide which medical interventions to provide (106;90%) and how to transport a patient (74;67%). However, after completing the cases, similar proportions of paramedics agreed (42;36%), disagreed (43;36%) or were neutral (30;25%) when asked if they find the POLST confusing. Conclusion The POLST is a powerful tool for paramedics when caring patients with serious illness. Although paramedics are confident in their ability to use a POLST to decide appropriate medical interventions, many still find the POLST confusing particularly when making transportation decisions. Some paramedics rely on online medical oversight to provide guidance in challenging situations. Authors recommend further research of EMS POLST utilization and goal concordant care, dedicated paramedic POLST education, specific EMS hospice and palliative care protocols and better nomenclature for non-transport in order to improve care for patients with serious illness.